Cosecha de agua lluvia para aprovechamiento urbano en el Proyecto Educativo La Cometa y el Colegio Técnico Profesional Uladislao Gámez Solano - Navarro-Bianchini, María Lourdes (Instituto Tecnológico de Costa Rica, 2019)
Climate change represents a threat to humanity and natural systems, altering the rainfall regime, obtaining extreme scenarios, where there is abundance in certain sites and others with long periods of drought, influencing the quality of water and its availability to the population. Costa Rica has not been exempted from this situation, leading to weather imbalances and even significant monetary losses. Rainwater harvest constitutes one of the Low Impact Solutions, which seeks to reestablish the water cycle in an urban environment. This Final Graduation Project proposes a design for a rainwater harvesting system for La Cometa Educational Project and one for the Tirrases Professional Technical College, that can be used for non-drinking water uses. For this purpose, the supply and demand of rainwater was determined for both institutions, for the CTP Uladislao Gámez Solano a series of scenarios were proposed, which were subjected to a multicriteria evaluation to choose the scenario with the most feasibility for the institution, the hydraulic design of water distribution, the sizing of the storage tanks, as well as the collection of rainwater from the roofs were also products of the present project, and finally the total cost of investment for the proposed systems in each of the institutions was determined. For the CTP the Scenario C was chosen with a 81%, as the most effective to respond to the individual characteristics of the institution, which has two decentralized systems that supply two different groupings of the institution with two storage tanks , one of 65 m3 and another of 70 m3, the latter equal to the one obtained for La Cometa’s water harvesting system. Finally, an investment cost of CRC 19,865,149 was obtained for the CTP and of CRC 9,432,1512 for the La Cometa.
Proyecto Final de Graduación (Licenciatura en Ingeniería Ambiental) Instituto Tecnológico de Costa Rica, Escuela de Química, 2019.
Keywords: Agua; Lluvia; Demandas; Oferta; Cosecha; Diseño; Research Subject Categories::TECHNOLOGY::Other technology::Environmental engineering